Combination antimicrobial therapy: in vitro synergistic effect of anti-staphylococcal drug oxacillin with antimicrobial peptide nisin against Staphylococcus epidermidis clinical isolates and Staphylococcus aureus biofilms - Toktam Sharafi; Ezzat Allah Ghaemi; Maryam Rafiee; Abdollah Ardebili (BMC, 2024)
Abstract The ability of Staphylococcus epidermidis and S. aureus to form strong biofilm on plastic devices makes them the major pathogens associated with device-related infections (DRIs). Biofilm-embedded bacteria are more resistant to antibiotics, making biofilm infections very difficult to effectively treat. Here, we evaluate the in vitro activities of anti-staphylococcal drug oxacillin and antimicrobial peptide nisin, alone and in combination, against methicillin-resistant S. epidermidis (MRSE) clinical isolates and the methicillin-resistant S. aureus ATCC 43,300. The minimum inhibitory concentrations (MIC) and minimum biofilm eradication concentrations (MBEC) of oxacillin and nisin were determined using the microbroth dilution method. The anti-biofilm activities of oxacillin and nisin, alone or in combination, were evaluated. In addition, the effects of antimicrobial agents on the expression of icaA gene were examined by quantitative real-time PCR. MIC values for oxacillin and nisin ranged 4-8 µg/mL and 64-128 µg/mL, respectively. Oxacillin and nisin reduced biofilm biomass in all bacteria in a dose-dependent manner and this inhibitory effect was enhanced with combinatorial treatment. MBEC ranges for oxacillin and nisin were 2048-8192 µg/mL and 2048-4096 µg/mL, respectively. The addition of nisin significantly decreased the oxacillin MBECs from 8- to 32-fold in all bacteria. At the 1× MIC and 1/2× MIC, both oxacillin and nisin decreased significantly the expression of icaA gene in comparison with untreated control. When two antimicrobial agents were combined at 1/2× MIC concentration, the expression of icaA were significantly lower than when were used alone. Nisin/conventional oxacillin combination showed considerable anti-biofilm effects, including inhibition of biofilm formation, eradication of mature biofilm, and down-regulation of biofilm-related genes, proposing its applications for treating or preventing staphylococcal biofilm-associated infections, including device-related infections.